Wideband absorption with polarization and angular insensitive metamaterial for optical applications based on Tungsten-SiO2 composites - Md Raihan; Saif Hannan; Md Ismail Haque; Mohamed Ouda; Abdulmajeed M. Alenezi; Mohamed S. Soliman; Mohammad Tariqul Islam (Journal of Science: Advanced Materials and Devices)
Energy harvesting from solar light is a matter of interest nowadays. In this discipline, researchers are attempting to achieve significant success in this field at a low cost and with minimal effort. To harness this solar energy, metamaterial absorbers (MMA) demonstrated a simple new method to collect these electromagnetic (EM) waves for use in solar energy. Furthermore, broadband absorbers are the best alternative for properly using solar energy. In this paper, we propose a shield pattern of Martii-shaped metamaterial absorber with polarization-insensitive for an optical regime made of dielectric material silicon dioxide (SiO2) and the metal tungsten (W), which serves as the top resonant material and back blocking plate. A 96.93 % average absorption rate was found for visible 380 nm–700 nm, along with a maximum peak absorption point at 604.53 nm, which is 99.996 %. Moreover, above 99 % absorption was found for 561.6–650.16 nm, and from 601 to 608 nm, the rate is above 99.99 %. Our MMA exhibits excellent average absorption of 96.27 % throughout the whole operation band range of 360 nm–1200 nm in TE and TM mode. Additionally, it is independent of polarization and incident angle. Its strong absorption and other properties make it well-suited for photonic applications, particularly in solar photovoltaics (PV), sensors etc.